APPRAISAL OF CONDITIONAL ATTRIBUTES OF RESIDENTIAL BUILDINGS IN AKURE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The situation of residential buildings in urban areas must be assessed to ascertain their form and age, functions, convenience, and liveability. As a result, this paper evaluates selected aspects of the condition of residential buildings in Akure, Nigeria. The study's objectives include examining the types of housing units, plot coverage, the number of rooms, and building setbacks. Other factors include housing tenure, the condition of the in-house tap, the type of toilet facilities, and the age of the buildings. The study drew on both primary and secondary data sources. A total of 1,369 people were polled, with 684, 480, and 205 representing the core, transition, and peripheral zones. According to the findings, tenement buildings accounted for 62.3 percent of Akure's residential buildings. In the city core, 88.6 percent of the respondents developed their lands above 50 percent, while 20.0 percent developed their lands above 50 percent on the outskirts. The paper suggests that the relevant stakeholders should enforce the subsisting building regulations, introduce environmental inspectors and mobile courts, and the Ondo State government should invest in urban infrastructure.
Keywords: Condition, Enforcement, Facility, Regulations, Residential buildings